The Regulatory Regime for Broadcasting Inappropriate Television Dramas Program Content for Adolescence Audience: Exclusive Study on Sexual Violence - อินเอียด, นายวิชิตโชค (Journal of Digital Communications, 2017)
inappropriate television soft operas, or those that violate Section 37 of the Broadcasting Act B.E. 2551, and (2) to explore and propose feasible amendments to the laws pertaining to the regulation of television soft operas. The aforementioned purposes are achieved by conducting research on theories and laws, as well as the participation of regulatory bodies relating to the content of television drama, in order to form a solution to the issues on inappropriate television soap opera. The author finds that, even though the Office of the National Broadcasting and Telecommunication Commission has issued an official notification on guidelines of television program adequacy ratings pertaining to the National Broadcasting and Telecommunication Commission’s Official Notification on Regulations of Program Scheduling in Broadcasting Services B.E. 2556, as the rules governing the regulations of content which consist of sexual, explicit language, violence, but there are still complaints on contents that are inappropriate for adolescents, for instance, a scene of sexual intercourse, a school scene featuring students fighting over love interest, and a fighting scene where a female character’s face was press against the exhaust pipe of a motorcycle and disfigured, some of which cases violate Section 37 of the Broadcasting Act B.E. 2551. Therefore, the author decides to conduct a study to explore an adequate course of regulation for television soap opera which would enable an extent of verification as to the adequacy of the content before the program is aired.